Centrilobular zonal necrosis as a hallmark of a distinctive subtype of autoimmune hepatitis. Issue 4 (April 2016) - Aizawa, Yoshio; Abe, Hiroshi; Sugita, Tomonori; Seki, Nobuyoshi; Chuganji, Yoshimichi; Furumoto, Youhei; Sakata, Akihiko
Abstract : Background and aim: Centrilobular zonal necrosis (CZN) is a known histological variant of autoimmune hepatitis (AIH). However, the significance of CZN is yet to be fully elucidated. This study aimed to determine whether CZN is a hallmark of a distinctive subtype of AIH. Methods: Histological changes in the centrilobular zones of liver biopsies from 113 AIH patients were assessed by a single pathologist and classified into three categories: typical zonal necrosis defined as CZN (15 patients); other necroinflammatory change (NIC; 24 patients); and absence of necrosis (non-NIC; 74 patients). The clinicopathological features and immunogenetic background of CZN patients were then assessed. Results: The clinicopathological features of AIH with CZN were distinct from other types of AIH, including a higher frequency of acute onset, lower frequency of antinuclear antibodies, lower antinuclear antibody titers, lower serum immunoglobulin G levels, lower grade interface hepatitis, less prominent lymphoplasmacytic infiltration, and lower AIH score. Increased and decreased frequencies of HLA-DR9 and HLA-DR4, respectively, were identified as immunogenetic features of AIH with CZN. Conversely, the clinicopathological characteristics of AIH with NIC were similar to those of non-NIC AIH, including the majority of the AIH patients. The therapeutic outcomes of AIH with CZN were excellent when precise diagnoses were made without delay. Conclusion: The clinicopathological features and immunogenetic background of AIH with CZN differed from AIH without CZN. CZN may be a hallmark of a distinct subtype of AIH.